New data on the subfamily Opiinae (Hymenoptera: Braconidae) from Iran - Dolati, Sana; Talebi, Ali Asghar; Peris-Felipo, Francisco Javier; Farahani, Samira; Khayrandish, Mohammad (Zootaxa, 2021)
Specimens of the Opiinae subfamily (Hymenoptera: Braconidae) were collected using Malaise traps during 2010–2011 in Northern Iran (Alborz, Guilan, Mazandaran, Qazvin and Tehran provinces). A total of 32 species belonging to 12 genera were identified, of which 11 species are new records for the fauna of Iran: Apodesmia posticatae (Fischer, 1957), Apodesmia striatula (Fischer, 1957), Biosteres (Chilotrichia) advectus Papp, 1979, Bitomus (Bitomus) multipilis Fischer, 1990, Desmiostoma parvulum (Wesmael, 1835), Opius (Misophthora) rufimixtus Fischer, 1958, Opius (Opiothorax) phytobiae Fischer, 1959, Opius (Misophthora) mischa Fischer, 1968, Opius (Opiothorax) attributus Fischer, 1962, Phaedrotoma pseudonitida (Fahringer, 1943) and Utetes curtipectus (Fischer, 1958). In addition, 21 species are new provincial records. Local and global distributions of all 32 species as well as diagnostic characters of each of the newly recorded species are provided.